Acute effects of cochleostomy and electrode-array insertion on compound action potentials in normal-hearing guinea pigs - Jwair, Saad; Ramekers, Dyan; Thomeer, Hans G. X. M.; Versnel, Huib (Frontiers in Neuroscience, 2023)
Electrocochleography (ECochG) is increasingly used in cochlear implant (CI) surgery, in order to monitor the effect of insertion of the electrode array aiming to preserve residual hearing. However, obtained results are often difficult to interpret. Here we aim to relate changes in ECochG responses to acute trauma induced by different stages of cochlear implantation by performing ECochG at multiple time points during the procedure in normal-hearing guinea pigs. Eleven normal-hearing guinea pigs received a gold-ball electrode that was fixed in the round-window niche. ECochG recordings were performed during the four steps of cochlear implantation using the gold-ball electrode: (1) Bullostomy to expose the round window, (2) hand-drilling of 0.5 – 0.6 mm cochleostomy in the basal turn near the round window, (3) insertion of a short flexible electrode array, and (4) withdrawal of electrode array. Acoustical stimuli were tones varying in frequency (0.25 - 16 kHz) and sound level. The ECochG signal was primarily analyzed in terms of threshold, amplitude, and latency of the compound action potential (CAP). Midmodiolar sections of the implanted cochleas were analyzed in terms of trauma to hair cells, modiolar wall, osseous spiral lamina (OSL) and lateral wall. Animals were assigned to cochlear trauma categories: minimal (n=3), moderate (n=5) or severe (n=3). After cochleostomy and array insertion, CAP threshold shifts increased with trauma severity. At each stage a threshold shift at high frequencies (4-16 kHz) was accompanied with a threshold shift at low frequencies (0.25–2 kHz) that was 10-20 dB smaller. Withdrawal of the array led to a further worsening of responses, which probably indicates that insertion and removal trauma affected the responses rather than the mere presence of the array. In two instances, CAP threshold shifts were considerably larger than thresholds of cochlear microphonics, which could be explained by neural damage due to OSL fracture. A change in amplitudes at high sound levels was strongly correlated with threshold shifts, which is relevant for clinical ECochG performed at one sound level. We conclude that basal trauma caused by cochleostomy and/or array insertion should be minimized in order to preserve the low-frequency residual hearing of CI recipients.